The Effect of Profitability, Debt Policy, Dividend Policy and Investment Decisions on Company Value in the Consumer Goods Industry Listed on the Indonesia Stock Exchange 2015-2019 Period - Juli Anggelika; Ferdinand Napitupulu (Institute of Computer Science (IOCS), 2021)
Management Study Program Faculty of Economics, University of Prima Indonesia Companies engaged in the food and beverage industry are included in the category of manufacturing companies that process raw materials into finished goods so that they have a selling value in the community. The purpose of this study was to determine the effect of profitability, debt policy, dividend policy and investment decisions on company value in the Consumer Goods Industry listed on the Indonesia Stock Exchange for the 2015-2019 Period. This research uses quantitative research methods because the research data is in the form of numbers and is analyzed using statistics and is causal in nature. The population in this research on the consumer goods industry listed on the Indonesia Stock Exchange is 51 in the Consumer Goods Industry for the 2015-2019 period. The sample of this research is 17 companies with 85 financial reports. The result is that Profitability has an effect on Firm Value in the Consumer Goods Industry which is listed on the Indonesia Stock Exchange. Debt Policy has an effect on Firm Value in the Consumer Goods Industry listed on the Indonesia Stock Exchange. Dividend Policy has no effect on Firm Value in the Consumer Goods Industry listed on the Indonesia Stock Exchange. Investment Decisions have no effect on Firm Value in the Consumer Goods Industry which is listed on the Indonesia Stock Exchange. Profitability, Debt Policy, Dividend Policy and Investment Decisions have an effect on Firm Value in the Consumer Goods Industry listed on the Indonesia Stock Exchange.